The Implementation of Children's Literacy and Numeracy Learning in the Early Childhood Education Curriculum - Sri Wahyuni; Nurafni Umayyah; Saudah Saudah (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2026)
This study aims to analyze the implementation of early childhood literacy and numeracy learning in the early childhood education curriculum in Indonesia and understand the various factors that affect its implementation. The research is motivated by the fact that there is still a tendency for literacy and numeracy learning to be formally academically oriented, so that it is not fully in accordance with the principles of early childhood development. The research uses a qualitative approach with a case study type to gain an in-depth understanding of learning practices in the field. Data were collected through semi-structured interviews, participatory observations, and documentation of selected early childhood teachers, principals, and parents using purposive and snowball sampling techniques. Data analysis was carried out using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of literacy and numeracy learning is carried out through a play approach, contextual experience, and exploration of the children's learning environment. The findings of the study reveal three main themes, namely literacy and numeracy learning as contextual learning experiences, implementation challenges due to parents' academic demands, and the importance of family involvement in supporting children's ability development. In addition, the use of digital media has also begun to be used to increase children's interest in learning, although it still requires the right assistance. This research provides a theoretical contribution in strengthening the perspective of social constructivism in early childhood learning and provides practical implications for teachers and policymakers in developing literacy and numeracy learning that is more contextual, humanistic, and in accordance with the characteristics of child development.